Salary history and employer demand: Evidence from a two-sided audit - Amanda Agan; Bo Cowgill; Laura K. Gee (W.E. Upjohn Institute for Employment Research, 2022)
We study how salary history disclosures affect employer demand, and how salary history bans shape hiring and wages. We show how these effects depend on the properties of the labor market, and we measure the key properties using a novel, two-sided field experiment. Our field experiment features hundreds of recruiters reviewing more than 2, 000 job applications. We randomize the presence of salary history questions as well as job candidates' disclosures. We find that employers make negative inferences about nondisclosing candidates, and that they anticipate positive selection into disclosure. Recruiters view salary history as a stronger signal about competing options than about worker quality. Disclosures by men (and other highly paid candidates) yield higher salary offers; however, they are negative signals of the value (net of salary) that a worker brings to the firm, and thus they yield fewer callbacks. While disclosures (especially of high amounts) generally increase recruiter beliefs about quality and competing offers, male wage premiums are regarded as a weaker signal of quality than other sources (such as the premiums from working at higher-paying firms or being well paid compared to peers). Recruiters correctly anticipate that women are less likely to disclose salary history at any level, and thus they punish women less than men for silence. When we simulate the effect of salary history bans using our results, we find muted effects on callbacks. Gender inequality in salary offers is reduced; however, equality comes at the expense of lower salaries overall (and especially for men).
Keywords: J71; M51; C93; 330; blinding; disclosure; recruiting; statistical discrimination; salary history; field experiments